Determinasi Pertumbuhan Ekonomi Daerah: Studi Empiris Kabupaten/Kota di Provinsi Riau - Angraini, Nofia; Handra, Hefrizal; Andrianus, Fery (SAFE-Network, 2025)
This study aims to analyze the effect of poverty, the Human Development Index, and unemployment on economic growth in the districts and cities of Riau Province over the period 2015–2024. The research employs a quantitative method using multiple linear regression with panel data covering 12 districts/cities in the province. The data analyzed include key macroeconomic indicators, namely the poverty rate, HDI, and open unemployment rate. The results show that poverty and HDI have a positive and significant effect on economic growth. In contrast, the unemployment rate has a negative and significant effect on regional economic growth. Simultaneously, these three independent variables explain 34.6% of the variation in regional economic growth, while the remaining portion is influenced by other factors not included in the model. These findings offer important implications for regional development policy. The positive relationship between poverty and economic growth indicates signs of unequal distribution of development outcomes, suggesting that economic growth has not been fully enjoyed by all segments of society. Therefore, local governments are encouraged to prioritize development policies that are more inclusive and socially equitable. It is recommended that investment be strengthened in the education, health, and employment sectors, along with the development of local potentials that can absorb labor and sustainably reduce poverty.